Efeitos cardiopulmonares e antinociceptivos da infusão contínua de fentanil, dexmedetomidina ou maropitant em cadelas submetidas à ovariohisterectomia - Velasquez, Omar Gutierrez (2020)
The study aimed to evaluate and compare the cardiorespiratory and analgesic parameters of continuous infusion of fentanyl, dexmedetomidine or maropitant in dogs submitted to ovariohysterectomy. Thirty healthy mixed breed bitches with an average body weight of 11±1.78 kg were evaluated. All animals received acepromazine (0.05 mg kg-1) intramuscularly as pre-anesthetic medication, anesthetic induction was performed with intravenous administration of propofol (5.51±0.67 mg kg-1), and anesthesia was maintained with isoflurane. Ten minutes after stabilization, continuous infusion was instituted, preceded by a bolus dose of the drugs evaluated, divided into the following groups: GF (fentanyl 2.0 g kg-1, 3.0 g kg-1 h- 1, n = 10), GD (dexmedetomidine 0.5 g kg-1, 1.0 g kg-1 h-1, n = 10) and GM (maropitant 1 mg kg-1, 150 g kg-1 h-1, n = 10). In the trans-operative period, cardiorespiratory parameters (HR, f, SBP, DBP, MBP, ETCO2, SpO2 and T° C) and analysis of arterial blood gases (pH, PaO2, PaCO2 and HCO3¯) were evaluated. Likewise, analgesic effects were assessed during surgery (trans-operatively) and after (post-operatively), recording cardiorespiratory parameters (HR, f, SBP, DBP, MBP) and using pain scales from the University of Melbourne (EDUM) and the Glasgow scale (EDG), respectively. In the evaluation of cardiorespiratory parameters, at some times, it was observed: lower HR in the GF and in the GD in relation to the baseline and the GM. However, the GF was larger compared to the GD. Blood pressure, compared to baseline, increased in the GF and the GD. Regarding the groups, the GF had lower blood pressure than the GD and higher blood pressure compared to the GM, while the GD was higher compared to the GM in blood pressure. The T° C, in relation to baseline, decreased in GD, GF and GM. in relation to f, ETCO2 and SpO2, there were no significant differences. In the measurements of arterial blood gas variables, there was a decrease in PO2 in the GF in relation to blood samples, while in the other variables pH, PCO2 and HCO3¯ there were no significant differences. The cardiorespiratory variables recorded for analgesic evaluation showed differences in time and between groups with greater pharmacological effect of each drug than with surgical nociceptive effects. In the postoperative analgesic evaluation, there were lower scores on the EDG in the GF, in the GD and in the GM compared to the first evaluation. In relation to the groups, there were lower scores in the GD and in the GM on the EDUM compared to the GF. From the results presented, it is suggested that the continuous infusion of maropitant has trans and postoperative antinociceptive effects, with few changes in cardiopulmonary parameters compared to the continuous infusion of dexmedetomidine or fentanyl